Conventional and combination topical photodynamic therapy for basal cell carcinoma: systematic review and meta‐analysis3. (9th September 2018) - Collier, N.J.; Haylett, A.K.; Wong, T.H.; Morton, C.A.; Ibbotson, S.H.; McKenna, K.E.; Mallipeddi, R.; Moseley, H.; Seukeran, D.; Ward, K.A.; Mohd Mustapa, M.F.; Exton, L.S.; et al.
Summary: Background: Topical photodynamic therapy (PDT) is an established treatment option for low‐risk basal cell carcinoma (BCC). Objectives: To compare efficacy, cosmesis and tolerability of PDT for BCC with alternative treatments. Methods: MEDLINE, PubMed, Embase and CENTRAL databases were searched from inception until 1 September 2017. Included studies were randomized controlled trials (RCTs) of PDT for nodular (n) and superficial (s) BCC reporting at least one of the following outcomes: clearance at 3 months and sustained at 1 or 5 years; recurrence at ≥ 1 year; cosmesis; adverse events; tolerability. Results: From 2331 search results, 15 RCTs (2327 patients; 3509 BCCs) were included. PDT efficacy (5‐year sustained clearance) was high but inferior to excisional surgery [nBCC pooled risk ratio (RR) 0·76; 95% confidence interval (CI) 0·63–0·91], and without re‐treatment of partially responding lesions, was modestly inferior to imiquimod (sBCC: RR 0·81; 95% CI 0·70–0·95) and similar to fluorouracil (sBCC: RR 0·88; 95% CI 0·75–1·04). Five‐year sustained clearance was inferior with conventional vs. fractionated PDT (sBCC: RR 0·76; 95% CI 0·68–0·84). PDT cosmesis was superior to surgery (sBCC: RR 1·68, 95% CI 1·32–2·14; nBCC: RR 1·82, 95% CI 1·19–2·80) and cryosurgery (BCC: RR 3·73, 95% CI 1·96–7·07), and without re‐treatment of partially responding lesions was similar to imiquimod (sBCC: RR 1·01, 95% CI 0·85–1·19) and fluorouracil (sBCC: RR 1·04, 95% CI 0·88–1·24). Peak pain was higher but of shorter duration with PDT than topical treatments. Serious adverse reactions were rarer with PDT than imiquimod (sBCC: RR 0·05, 95% CI 0·00–0·84) and fluorouracil (sBCC: RR 0·11, 95% CI 0·01–2·04). Combination PDT regimens demonstrated reduced recurrence and improved cosmesis; however, results from these small studies were often nonsignificant. Conclusions: PDT is an effective treatment for low‐risk BCC, with excellent cosmesis and safety. Imiquimod has higher efficacy than single‐cycle PDT but more adverse effects. Highest efficacy is with excisional surgery. Fractionated and combination PDT options warrant further study. Abstract : What's already known about this topic Topical photodynamic therapy (PDT) is one of a range of established treatment options for low‐risk basal cell carcinoma (BCC). BCC clearance is reported to be higher with imiquimod than with single‐cycle PDT. What does this study add? This is the largest systematic review and meta‐analysis to date of PDT for BCC and incorporates National Institute for Health and Care Excellence‐approved GRADE assessment of evidence quality, including 15 RCTs (2327 patients with 3509 BCCs). Serious adverse reactions are less common with PDT than with imiquimod. Peak pain is higher with PDT than topical therapies but is of shorter duration. Fractionated PDT offers superior clearance to conventional PDT. Combination PDT treatments show promise but require further study. Linked Editorial:  Lim. Br J Dermatol 2018;179 :1240–1241 . Plain language summary available online